Historia doctrinae catholicae inter armenos unionisque eorum cum ecclesia Romana in concilio Florentino - Balgy, Alexandro (My University, 1878)
The book is devoted to the attempts to unite the Armenian Church with the Roman Catholic Church, especially in the context of the Council of Florence
Alexandro Balgy. - Viennae : Congr. Mechitharisticae (W. Heinrich), 1878. - x, 374 p. ; 22 cm.
Keywords: Armenian Apostolic church; Church history-Middle ages; Armenia-History